Comparative Study of Regional Development Before and After The Trans Sumatera Toll Road (Case Study Lampung Province) - Haris Haris; Rully Indrawan; Juliater Simarmata; Zulfa Fitri Ikatrinasari (Dinasti International Journal of Education Management And Social Science, 2024)
The Central Statistics Agency (BPS) records that the economic growth in Lampung Province has experienced a lower growth rate compared to the national economic growth. This condition is exacerbated by the lack of development in existing infrastructure, especially provincial roads that have suffered severe damage. In this context, the provision of toll road infrastructure becomes crucial in regional development as it serves as a means to facilitate and support community activities. This study aims to analyze the differences in the Gross Regional Domestic Product (GRDP) of transportation and warehousing, tourism, agriculture, forestry and fisheries, Regional Original Income (PAD), and economic growth of districts in Lampung Province before and after the existence of the Trans-Sumatra Toll Road. The research method used is a quantitative approach using five variables, namely Transportation and Warehousing, Tourism, Agriculture, Forestry and Fisheries, Regional Original Income, and Economic Growth. Secondary data related to these variables were collected, especially those related to transportation and warehousing, tourism, agriculture, forestry and fisheries, regional original income, and economic growth. The study involved six Districts/Cities in Lampung Province traversed by the Trans-Sumatra Toll Road, namely South Lampung, Central Lampung, Mesuji, Pesawaran, Tulang Bawang, and West Tulang Bawang. Observation samples were collected for 4 years before and 4 years after the existence of the Trans-Sumatra Toll Road for the period 2015-2022. The collected data was then processed using SPSS Ver. 26 software. The results of the study indicate that the existence of the Trans-Sumatra toll road in several districts of Lampung Province has a significant impact on various economic sectors and Regional Original Income (PAD). The presence of significant average differences indicates that the Trans-Sumatra toll road has had a considerable impact on the economic sector and Regional Original Income in the mentioned districts.